Perancangan Aplikasi Sistem Informasi Pengolahan Nilai Siswa dengan Metode Rapid Application Development (RAD) Studi Kasus pada Madrasah Aliyah Saadatuddarain menggunakan Dreamweaver dan MySQL - Arfan, Fadlan; Faizah, NM; Rakryan WP, Ryan (Journal Innovations Computer Science, 2023)
Web-Based Student Grade Data Processing Information System is a system that provides online student activity report information, focusing on grade reports and student-related information. This research was conducted at Madrasah Aliyah (MA) Sa'adatuddarain, Jalan Mampang Raya No. 103, South Jakarta. The main problem faced by MA Sa'adatuddarain is the processing of student score data which is still done manually using Microsoft Excel. The results are then collected into the new curriculum section and submitted to the homeroom teacher in the form of sheets of paper. Therefore, an information system is needed that can manage data on student learning outcomes more effectively and efficiently. This research aims to develop a web-based information system application for processing data on student learning outcomes. The method applied in this research is Rapid Application Development (RAD) using the MySQL Database and implemented using Adobe Dreamweaver. The programming language used involves PHP (Pre-Hypertext Processor), CSS (Cascading Style Sheet), and Web. The result of this research is "Processing Student Grades at MA Sa'adatuddarain", an application equipped with various features for Class Teachers and Students, presenting information including grades and student attendance at MA Sa'adatuddarain.